Practices and conditions of teacher collaboration : case study of a Greek primary school - Tsalidi, Aikaterini (2019)
In this study, teacher collaboration is examined in the context of a Greek primary school, using various prisms and angles, providing insight regarding the teachers’ perceptions, practices and inner expectations. The study consists of views and perceptions stemming from ten Greek teachers and the principal of a primary school located on the island of Rodos, Greece. All the research subjects are teachers from different backgrounds, both professional and personal, with various years of teaching experience. The data for this study were collected through individual interviews and observation notes over a period of ten school days. The main goal is to report the teachers’ insights regarding their collaboration, as well as address the underlying issues and prerequisites that would implement it further into their practices. A qualitative, content analysis method was then used upon the extracted data according to the demands of the research questions. The findings indicate a causal relationship between teacher collaboration and well-established collegial relationships, which sets the foundations for the creation of collaborative cultures among teachers. Connecting to the above is the direct involvement of the administration which acts as balancing, motivating and leading factor that provides guidance and stability. Finally, the results highlight the need for structured training, curriculum reforms and proper infrastructure which act as prerequisites and ultimately set the base for collaboration to flourish among Greek teachers. Existing literature is examined in contrast to the findings, a process which provides a clear image of validation, contradiction or supplementation between them. The study’s insights provide information on curriculum reforms, collegial relationships, tools and infrastructure, the principal’s role and specialized training, as far as substantial teacher collaboration is concerned in the Greek school context.